Meningkatkan Minat Belajar Tari Kreasi Manuk Dadali Melalui Penggunaan Media Audiovisual pada Siswa Kelas VI di SDN 1 Cibeber Kecamatan Cikalong Kabupaten Tasikmalaya - Putriana, Neng Ima; Ahmad Wakih, Agus; Haris Mahendra , Hatma (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the planning for increasing interest in learning, implementation of increasing interest in learning, and increasing student’s interest in learning in Arts, Culture and Crafts learning after using audiovisual media in class VI SDN I Cibeber, Cikalong District, Tasikmalaya Regency. The type of research used in Classroom Action Research using audiovisual media. Learning is carried out through two cycles. The object of research is the application of audiovisual dance media created by Manuk Dadali with the research subjects, namely 15 class VI students at SDN 1 Cibeber Cikalong District Tasikmalaya Regency. Data was collected using observation, interviews, and documentation methods. The result of the research after the use of audiovisual showed an increase in student’s interest in learning the dance art Manuk Dadali.